Top management commitment for successful small and medium-enterprises(SMEs): A hoax or a reality? - Caroline, Ndiritu; Harriet, Kidombo; Anne, Ndiritu (European Scientific Journal, ESJ, 2016)
The role of small and medium enterprises in any country’s economic development cannot be under estimated. It is important for all countries especially the developing ones to note that the key to having a sustained development is to improve the performance of small and medium enterprises (SMEs). This ensures economic growth is inclusive of all people. The success of these enterprises should be the concern of all governments that are interested in not only alleviating poverty as a major threat to sustainable development. The purpose of this study was to investigate the influence of top management commitment as a Total Quality Management (TQM) practice on performance of small and medium enterprises. The study concentrated on youth group projects in Kajiado north sub county, Kajiado County, Kenya. Youth projects were randomly selected from Kajiado north sub-county, in five wards. The study used mixed method approach in the data collection and analysis, to capture both the qualitative and quantitative data. The design is descriptive. The target population was 210 youth that were involved in youth group projects. Spearman’s correlation was used to test the relationship between the variables. The analyses indicated that there is significant relationship between top management and performance.